Representasi Ikhlas dalam Film Hafalan Shalat Delisa: Analisis Perspektif Tasawuf Al-Ghazali - Alya Mukhbita; Carissa Maharani; Siti Alifia Ananda; Dadan Firdaus (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the representation of the concept of ikhlas (sincerity) in the film Hafalan Shalat Delisa from a Sufism (tasawuf) perspective. Using a qualitative descriptive-analytical approach with content analysis method, this study analyzes the scenes, dialogues, and character development of the main protagonist to identify the forms of ikhlas representation found in the film. The theoretical framework employed is the concept of ikhlas in Al-Ghazali's Sufi perspective, particularly the spiritual maqamat framework encompassing patience (sabar), reliance on God (tawakal), and acceptance (ridha). The results show that ikhlas in this film is represented through four interrelated dimensions: (1) ikhlas in worship, reflected in the transformation of the protagonist Delisa's motivation in memorizing prayer recitations from material orientation toward sincerity of intention for the sake of Allah; (2) ikhlas in patience, presented through the character's inner response to the layered losses caused by the tsunami disaster; (3) ikhlas in tawakal, displayed through the character's struggle to rise again while fully surrendering the outcome to Allah; and (4) ikhlas in ridha, as the culmination of the spiritual journey manifested in sincere heartfelt acceptance of Allah's decree. These findings affirm that the film Hafalan Shalat Delisa functions not merely as religiously themed entertainment, but also as a cultural text that authentically represents Sufi spiritual values through a coherent cinematic narrative.